Taxonomy and Diversity of Genus Pediastrum Meyen (Chlorophyceae, Algae) in East Nepal - Rai, S.K.; Misra, P.K. (Our Nature, 2013)
Pediastrum Meyen is a green algae occurs frequently in lentic environment like pond, puddles, lakes etc. mostly in warm and humid terai region. Twenty taxa of Pediasturm have been reported from Nepal, mostly from central and western part of the country, hitherto. Among them, in the present study, ten taxa of Pediastrum are enumerated also from east Nepal. Taxonomy and diversity of each taxa have been described with photomicrography. DOI: http://dx.doi.org/10.3126/on.v10i1.7779